2018
DOI: 10.1016/j.jpdc.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Scalable system scheduling for HPC and big data

Abstract: In the rapidly expanding field of parallel processing, job schedulers are the "operating systems" of modern big data architectures and supercomputing systems. Job schedulers allocate computing resources and control the execution of processes on those resources. Historically, job schedulers were the domain of supercomputers, and job schedulers were designed to run massive, long-running computations over days and weeks. More recently, big data workloads have created a need for a new class of computations consist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 39 publications
0
50
0
1
Order By: Relevance
“…It manages different compute jobs related to different users on homogenous or heterogeneous computational resources. It can have different names that reflect the same mechanism such as scheduler, resource manager, resource management system (RMS), and a distributed resource management system (D-RMS) [7]. Despite significant growth in terms of heterogeneity of resources and job complexity and diversity, job schedulers still have the main core function of job queuing, scheduling and resource allocation, and resource management [8] [9].…”
Section: Related Workmentioning
confidence: 99%
“…It manages different compute jobs related to different users on homogenous or heterogeneous computational resources. It can have different names that reflect the same mechanism such as scheduler, resource manager, resource management system (RMS), and a distributed resource management system (D-RMS) [7]. Despite significant growth in terms of heterogeneity of resources and job complexity and diversity, job schedulers still have the main core function of job queuing, scheduling and resource allocation, and resource management [8] [9].…”
Section: Related Workmentioning
confidence: 99%
“…Recent experiments have shown that the naive, serial job submission performance of a modern job scheduler can significantly slow down processing for jobs with a very large number of tasks [24]. To achieve maximal job launch performance for large HPC (high performance computing) or HPDA (high performance data analysis) jobs requires employing a technique known as multilevel scheduling which involves modifying our analysis code slightly to be able to process multiple datasets or files with a single job launch [25].…”
Section: Llmapreduce: Multi-level Map-reducementioning
confidence: 99%
“…By leveraging supercomputing and big data storage assets the LLSC has built the MIT SuperCloud, a coherent fusion Fig. 3: Schematic depicting key components of a canonical cluster scheduler including job lifecycle management, resource management, task scheduling and job execution (adapted from [25]). The SLURM scheduler used on the MIT SuperCloud systems behaves according to this model.…”
Section: Experimental Environmentmentioning
confidence: 99%
“…The passport consists of a parallel program, input data and system requirements (number of cores or nodes, amount of RAM) and execution time limit. S Special software [1] like SLURM [2], PBS [3] or the Russian native job management system SUPPZ [4] manage jobs in supercomputers. The kernel of any job management system (JMS) is the scheduler.…”
Section: Introductionmentioning
confidence: 99%